Flush Cairan pada Jarum Spinal 27-Gauge Tipe Quincke Mempercepat Waktu Munculnya Cerebrospinal Fluid (CSF) sebagai Penanda Keberhasilan Mencapai Ruang Subarakhnoid pada Tindakan Anestesi Spinal - Muhammad Jalaluddin Assuyuthi Chalil (ANATOMICA MEDICAL JOURNAL | AMJ, 2019)
ABSTRACT Background: There are currently various sizes and shapes of spinal needles designed to prevent post-dural puncture headache (PDPH). Spontaneous CSF flow is very slow on fine spinal needles which impacts prolonging the duration of the procedure and resulting in repeated punctures in the dura mater. Aim. To Evaluate 0.5% 0.2 mL bupivacaine filling into the Quincke 27G needle before insertion is a fast and simple method for identifying the appearance of CSF under spinal anesthesia.Methodology. After obtaining approval from the ethics committee, a cross-sectional study was conducted on 100 pregnant women, aged 18-40 years, ASA I and II status, who underwent elective cesarean section, and sought written approval. Subjects were randomized into 2 groups. A (n = 50) used a 27G Quincke spinal needle (Spinocan®, B.Braun Melsunger) filled with 0.5% bupivacaine 0.2 ml before being inserted into the L3-L4 space and group B (n = 50) as a control. The time from when the stylet was pulled until the appearance of CSF on the hub was calculated using a stopwatch.Results. There were no significant differences between the two groups in age and ASA physical status. The mean time for CSF to appear was significantly shorter in group A than in group B (6.26 vs 16 seconds; p= 0.000).Conclusion. This method can be used to identify the emergence of CSF in a shorter of time, simpler and easier to do.Keywords: fine spinal needle, cerebrospinalfluid (CSF), post-dural puncture headache (PDPH)